Framing the 'White Widow': Using intersectionality to uncover complex representations of female terrorism in news media. (September 2019) - Auer, Meagan; Sutcliffe, John; Lee, Martha
Following 21 September 2013, news media in the UK offered extensive and elaborate coverage of the Westgate Mall Massacre in Nairobi, Kenya. This act of terrorism, perpetrated by Al-Shabaab, left over 60 people dead. What news media considered particularly captivating was not the devastation of the attack, but the suspected involvement of Samantha Lewthwaite. She remained at the center of news media in Britain for several months after the attack, dubbed the 'White Widow'. In this article, the authors employ an intersectional approach to explore the ways that race, religion, nationality, age, class, and gender converge in mediated representations of Lewthwaite. They argue that the application of intersectionality results in a more holistic understanding of the content and discursive impact of news narratives about female terrorists and find that news media both vilify and normalize Lewthwaite, representing her participation in terrorism through complex constellations of identity.